Per Operative Discovery of Placenta Percreta and Uterine Rupture at 37 Weeks of Gestation - A Case Report (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
The aim is to publish this case report of rarely occurring and life threatening condition, placenta percreta causing uterine rupture at 37 weeks of gestation. A second gravida with unevenful pregnancy was admitted in a tertiary hospital at her 37 weeks of gestation with lower abdominal pain and less foetal movement with history of one caesarean section.After admission she complaint of dull pain in whole abdomen which was gradually increasing in intensity, associated with hardening of uterus , initiallyher pulse and BP was stable,but later she had tachycardia and fetal heart rate was irregular.An emergency cesarean section was done. Immediately after opening the peritoneal cavity a perforation in uterine wall by placenta was found through which active bleeding was present.After holding the bleeding point,an incision in upper segment of uterine wall was given and an asphyxiated male baby was delivered by breech extraction. Then in presence of a senior gynaecologist caesarean hysterectomy was done keeping placenta in situ.Post operative period was uneventful for the mother but the baby was managed in neonatal care unit. Both of them were well during discharge. Placenta percreta is a rare pathological entity with challenging diagnostic and therapeutic requirement especially for resource limited settings.Bangladesh J Obstet Gynaecol, 2015; Vol. 30(1) : 49-52